Ankyloglossia: Diagnosis, Challenges, the Role of Frenotomy in Treatment – A Comprehensive Literature Review - Maja Weimann; Marta Janura; Martyna Byrska; Hanna Barska-Kobylińska; Grzegorz Przywara; Oliwia Biegańska; Emilia Biczak (Journal of Education, Health and Sport, 2025)
Introduction